Implantable Electrochemical Microsensors for In Vivo Monitoring of Animal Physiological Information - Zhou, Jin; Zhou, Shenghan; Fan, Peidi; Li, Xunjia; Ying, Yibin; Ping, Jianfeng; Pan, Yuxiang (Nano-Micro Letters, 2023)
In vivo monitoring of animal physiological information plays a crucial role in promptly alerting humans to potential diseases in animals and aiding in the exploration of mechanisms underlying human diseases. Currently, implantable electrochemical microsensors have emerged as a prominent area of research. These microsensors not only fulfill the technical requirements for monitoring animal physiological information but also offer an ideal platform for integration. They have been extensively studied for their ability to monitor animal physiological information in a minimally invasive manner, characterized by their bloodless, painless features, and exceptional performance. The development of implantable electrochemical microsensors for in vivo monitoring of animal physiological information has witnessed significant scientific and technological advancements through dedicated efforts. This review commenced with a comprehensive discussion of the construction of microsensors, including the materials utilized and the methods employed for fabrication. Following this, we proceeded to explore the various implantation technologies employed for electrochemical microsensors. In addition, a comprehensive overview was provided of the various applications of implantable electrochemical microsensors, specifically in the monitoring of diseases and the investigation of disease mechanisms. Lastly, a concise conclusion was conducted on the recent advancements and significant obstacles pertaining to the practical implementation of implantable electrochemical microsensors. Highlights: 1 The materials, fabrication methods, implantation technologies, and applications of implantable electrochemical microsensors for animals were summarized. 2 The implantable electrochemical microsensors for monitoring diseases and exploring disease mechanisms were discussed. 3 The current status, ongoing challenges, and future development prospects of implantable electrochemical microsensors in monitoring animal physiological information were highlighted.